The - Campbell, Gordon (Oxford University Press, 2006)
The Grove Encyclopedia of Decorative Arts covers thousands of years of decorative arts production throughout western and non-western culture. With over 1,000 entries, as well as hundreds drawn from the 34-volume Dictionary of Art, this topical collection is a valuable resource for those interested in the history, practice, and mechanics of the decorative arts. Accompanied by almost 100 color and more than 500 black and white illustrations, the 1,290 pages of this title include hundreds of entries on artists and craftsmen, the qualities and historic uses of materials, as well as concise definitions on art forms and style. Explore the works of Alvar Aalto, Charles and Ray Eames, and the Wiener Wekstatte, or delve into the history of Navajo blankets and wing chairs in thousands of entries on artists, craftsmen, designers, workshops, and decorative art forms